Topological optimization design of SLM additive manufactured unmanned aerial vehicle bearing joint structure based on variable density method - Shuaichao YUAN; Jianfeng WANG; Yuhang DUAN; Lujing HAO; Xiaohong ZHAN (工程科学学报)
To address the need for weight reduction in a large unmanned aerial vehicle (UAV) fuselage, this study focused on the load-bearing joint structure manufactured through selective laser melting (SLM). A finite element model of this structure was created and analyzed using ANSYS Workbench to evaluate its strength and stiffness under various extreme conditions. The design was verified against the material’s maximum permissible stress criterion. The study then employed topology optimization, using the variable density method aimed at minimizing stress, to optimize the joint structure while retaining 40% of its original mass. Based on the optimization results, two redesign schemes were developed and validated through static analysis. In the optimized models, significant material removal was observed in the middle part of the thin plate connected by the covers of Scheme I and Scheme II. The latter, in particular, demonstrated the largest side length of material removal at 56 mm. The weights of Scheme I and Scheme II were reduced to 0.325 kg and 0.327 kg, respectively, down from the initial mass of 0.377 kg, translating to weight reductions of 13.8% and 13.3%, respectively. The results indicated that Scheme II achieved a notable 13.3% weight reduction while maintaining the strongest load-bearing capacity among the alternatives. Under similar loading conditions, Scheme II exhibited lower stress concentration compared to Scheme I, with reductions of 21.6%, 5.0%, 20.6%, and 27.8% from working condition 1 to working condition 4, respectively. The “wide and short” aperture at the connecting plate helped disperse stress, enhancing load-bearing capacity while compromising on weight reduction. Additionally, Scheme II showed minimal deformation, with a minimum deformation of 0.16 mm, indicating higher stiffness and better resistance to deformation. This indicates that Scheme II is more efficient in maintaining structural integrity under load, making it a more viable option for the UAV fuselage’s load-bearing joint structure. This study demonstrates combining topology optimization with SLM can greatly shorten the manufacturing cycle and produce complex structural parts efficiently. This approach provides important theoretical guidance and reference for the lightweight design and manufacturing field of large-scale UAV load-bearing joint structures. The integration of these advanced techniques advances performance optimization and production efficiency in large-scale UAV load-bearing joint structures. Moreover, it promotes the innovation and development of aerospace manufacturing technology by enabling the creation of more efficient, lighter, and stronger components. Overall, the findings highlight the potential for significant advancements in UAV design and manufacturing, offering practical insights and methodologies applicable to similar engineering challenges in the aerospace industry. The research underscores the importance of adopting cutting-edge technologies such as SLM and topology optimization to achieve superior performance in aerospace applications.